Processing of social exclusion in a strict hierarchy - Michael Niedeggen; Rudolf Kerschreiter (PLoS ONE, 2025)
Exclusion is defined as a significant reduction of involvement or interaction with others. This threatens our social need for belonging and triggers a negative affective response. The response is associated with a P3 effect in the event-related brain potentials (ERP) indicating that the processing of exclusion is characterized by a violation of the expected social involvement. The majority of experimental findings relies on the Cyberball setup, in which two putative co-players exclude the participant in a virtual ball-tossing game. The current studies challenge the previous findings by introducing a novel paradigm, Cyberband , which simulates participation in an orchestra setting. Here, exclusion is defined by reducing the number of cues provided by a putative conductor. In experiment 1, the number of cues exclusively directed to the individual (solo) was reduced. In contrast to previous Cyberball findings, the self-reported threat to belonging as well as the P3 effect were clearly diminished. In experiment 2, participants were excluded from joint actions. Here, a reduced participation in common actions (tutti), but not in dyadic actions (duets), enhanced the P3 effect. In both experiments, the reduced participation primarily affected the expression of an early frontal ERP positivity (P2) indicating a change of cue salience. In sum, these results indicate that exclusion is processed differently if attributed to a single decider: The experience is reported to be less painful, and ERP signatures of a violation of the expected participation – prominent in the established Cyberball setup – are predominantly elicited by an exclusion from joint actions.